Retail Communication Mix to Strengthen the Competitiveness of MSMEs in the Digital Age - Hidayah, Nur; Desmawati, Erlinda; Tunru, Cathleen Anabel (International Journal of Social Science and Community Service, 2025)
The purpose of this activity is to provide guidance on the application of retail communication mix as a marketing strategy that can increase the competitiveness of Micro, Small and Medium Enterprises (MSMEs) in the digital era. In the context of increasingly fierce business competition, MSMEs are required to be more creative and innovative in reaching consumers. Retail communication mix, which consists of various elements such as new media and traditional media, is considered one of the keys to the success of a business. The activity was carried out with MSME partners engaged in the food sector. The main problem faced by partners was a lack of knowledge about using retail communication to maintain their competitiveness and existence. The methods used were initial observation and training. This activity is expected to contribute to the development of the partners' knowledge, particularly in the fields of management and retail marketing. In addition, the results of this activity are also expected to provide recommendations for partners in designing effective retail marketing strategies to increase their business competitiveness in the digital era.